EFEKTIVITAS WORKSHOP DARING DALAM PERSPEKTIF PENDIDIK SEBAGAI PENDEKATAN ANDRAGOGI - Valdi Giffari Rahmayati Putra; Kurnia Azizah; M. Alfan Aldiansyah (Universitas Islam Malang, 2023)
This study focuses on the perspective of workshop participants to determine its effectiveness. Thus, this study aims to determine the effectiveness of workshops conducted online through the perspective of the participating educators. In this study using descriptive qualitative research with a phenomenological design. The subjects of this study were 5 educators who had attended online workshops. Meanwhile, this research instrument uses interview guidelines. In the interview procedure, the researcher uses a type of structured interview. Through the aspects asked by the researcher in the interview, it can be concluded that there are 9 points where the answers are found, including; online workshops involve participants in the learning process, the material is appropriate or relevant to the needs of the participants, the workshop material is practical, the workshop time is still lacking in duration, the development of social feelings among participants, the training is given on target. Regarding the constraints of online workshops, including; internet connection, difficult time adjustment, lack of information. While the main motivation for participating in the workshop, including; the need for competency improvement as educators, the effects of the pandemic, time and place efficiency. Through the results and discussion that the researchers have described, it can be concluded that online workshops are effective from an educator's perspective.